2018
DOI: 10.1021/acsmacrolett.8b00278
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Confinement Slows Surface Fluctuations of Star Polymer Melt Films

Abstract: The unusually large film thickness at which confinement effects manifest themselves in surface fluctuations of unentangled four-arm star polymers has been defined using film thicknesses from 10R g to 107R g . For 15k four-arm star polystyrene (SPS), confinement appears at a thickness between 112 nm (40R g ) and 72 nm (26R g ), which is remarkably larger than the thicknesses at which confinement appears for unentangled 6k linear (<15 nm, <7R g ) and 6k and 14k cyclic (24 and 22 nm, respectively) polystyrenes. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Based on our experimental investigations, we attribute the ~45% faster physical aging response of ultra‐high MWs ≥ 6500 kg mol −1 thin PS films, relative to equivalent films of (merely) high MWs ≤ 3500 kg mol −1 , to a diminished gradient in dynamics near the free surface of these films. These results contribute to the growing reports in the literature that chain connectivity and entropy are additional factors influencing interfacial effects and dynamical gradients in thin films beyond the well‐characterized enthalpic interactions.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Based on our experimental investigations, we attribute the ~45% faster physical aging response of ultra‐high MWs ≥ 6500 kg mol −1 thin PS films, relative to equivalent films of (merely) high MWs ≤ 3500 kg mol −1 , to a diminished gradient in dynamics near the free surface of these films. These results contribute to the growing reports in the literature that chain connectivity and entropy are additional factors influencing interfacial effects and dynamical gradients in thin films beyond the well‐characterized enthalpic interactions.…”
Section: Discussionsupporting
confidence: 67%
“…However, several recent studies have reported differences in confinement behavior associated with chain length, stiffness, entanglements, and chain architecture that are unexpected given the primarily enthalpic understanding developed over the years. This suggests that entropic effects may also play a modifying role in understanding confinement effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, it has been reported that the dynamics of branched polymers in thin films is different from those of corresponding linear polymers. [ 33 36 ] This can be explained in terms of the entropic interaction between star‐shaped polystyrene (sPS) chains and the solid surface. [ 34 ] Also some studies showed that the suppressed relaxation dynamics of interfacial sPS chains could extend away from the Si/SiO x substrate over a length scale of several times larger than that for linear PS (lPS) chains.…”
Section: Sample Mn Pdi Rg [Nm] Tgb [K]mentioning
confidence: 99%
“…[ 34 ] Also some studies showed that the suppressed relaxation dynamics of interfacial sPS chains could extend away from the Si/SiO x substrate over a length scale of several times larger than that for linear PS (lPS) chains. [ 35,36 ] Despite such growing evidence of the fundamental role of molecular architecture in controlling the relaxation dynamics in a thin film, it seems that direct observations of the relaxation processes of interfacial chains have yet to be addressed.…”
Section: Sample Mn Pdi Rg [Nm] Tgb [K]mentioning
confidence: 99%